2021
DOI: 10.3390/fermentation7030111
|View full text |Cite
|
Sign up to set email alerts
|

Use of Corn-Steep Water Effluent as a Promising Substrate for Lactic Acid Production by Enterococcus faecium Strain WH51-1

Abstract: Various challenges facing the industrial production of bio-based lactic acid (LA) such as cost of raw materials and nitrogen sources, as well as contamination risk by mesophilic and neutrophilic producers, should be overcome for the commercial production. This study aimed to investigate the feasibility of corn steep water (CSW) as a raw material for LA production using a newly thermo-alkali-tolerant lactic acid bacterium. The physicochemical characteristics of CSW were investigated. The high carbohydrates, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 80 publications
0
16
1
Order By: Relevance
“…Pediococcus acidilactici, for instance, was engineered to use lignocellulosic biomass (corn stover and wheat straw) by Qiu et al [156,157], reaching high titers of D-lactic acid and L-lactic acid, with 97.3 and 130.8 g/L, respectively. The recent strategy to minimize contamination risk and facilitate non-sterilization lactic acid fermentation is using alkali-and thermo-tolerance strains [158]. They isolated Enterococcus faecium WH51-1, and successfully produced 44.6 g/L lactic acid with a yield of 0.89 g/g, from corn steep water at high temperature (45 • C) and pH (9.0).…”
Section: Lactic Acidmentioning
confidence: 99%
“…Pediococcus acidilactici, for instance, was engineered to use lignocellulosic biomass (corn stover and wheat straw) by Qiu et al [156,157], reaching high titers of D-lactic acid and L-lactic acid, with 97.3 and 130.8 g/L, respectively. The recent strategy to minimize contamination risk and facilitate non-sterilization lactic acid fermentation is using alkali-and thermo-tolerance strains [158]. They isolated Enterococcus faecium WH51-1, and successfully produced 44.6 g/L lactic acid with a yield of 0.89 g/g, from corn steep water at high temperature (45 • C) and pH (9.0).…”
Section: Lactic Acidmentioning
confidence: 99%
“…On the other hand, the addition of glycerol as an extra carbon source led to reducing the degradation percentages to 54.2%. The decreasing of biodegradation percentages in the presence of extra carbon sources with an increase of bacterial growth can be attributed to catabolite repression caused by extra carbon sources [46,47]. Interestingly, the L. cresolivuorans strain HIS7 exhibits high efficacy to degrade cypermethrin in the presence of different nitrogen sources.…”
Section: Optimizing Factors Affecting the Biodegradation Processmentioning
confidence: 99%
“…As an alternative cheap nitrogen source, many authors have demonstrated the utility of corn steep liquor (CSL), which is occurred in starch manufacturing process from corns [ 16 ] in lactic acid production. [ 17–20 ] Wee et al. [ 18 ] reported that the addition of 30 g L –1 of CSL could reduce the concentration of yeast extract to 1 g L –1 in l ‐lactic acid fermentation from starch hydrolysate using Enterococcus faecalis RKY1.…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative cheap nitrogen source, many authors have demonstrated the utility of corn steep liquor (CSL), which is occurred in starch manufacturing process from corns [16] in lactic acid production. [17][18][19][20] Wee et al [18] reported that the addition of 30 g L -1…”
Section: Introductionmentioning
confidence: 99%